Зарик - Лазаревна Сарьян, Катарине (Musical Armenia, 2010)
Dancer theaterologist, Lazar Saryan’s daughter Katarine Lazar Saryan in her “ The Zarik” article rebounds her father’s and grandfather’s boundless and deep respectful relationship’s description with warm love. Imminent expectation of son from war, filial care, rises the caring son’s picture is reader’s fancy. And also, how was son selecting apricots, fine fruits from the market, which later became still life in his father’s canvases. Daughter testifies that passing through the trials of the war, father: L.M. Saryan was remained courteous, kind, gentle and sensitive personality , which do not change over a quarter of a century of leading the Yerevan State Conservatory after Komitas.